2021
DOI: 10.1186/s12893-020-00977-4
|View full text |Cite
|
Sign up to set email alerts
|

Giant right ventricular myxoma presenting as right heart failure with systemic congestion: a rare case report

Abstract: Background Myxoma is an uncommon disease and its symptoms vary greatly depending on size, location and mobility. Right-sided myxoma, especially right ventricular myxoma, is much rarer, and the symptoms are alien and uncharacteristic. The lack of understandings poses challenges to prompt diagnosis and timely treatment. Case presentation A 44-year-old female patient was diagnosed with giant right ventricular tumor. Right heart failure and systemic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[11][12][13][14] Larger cardiac myxomas may cause similar hemodynamic abnormalities resulting in chylothorax. 15 In our case, the left atrial myxoma can float through the mitral valve into the left ventricle during diastole, causing mitral orifice obstruction like rheumatic mitral stenosis, which can gradually or suddenly result in congestion of systemic circulation and obstruction of lymphatic return, and eventually cause chylothorax. Furthermore, the chylothorax improved after oral diuretics were used to reduce pulmonary congestion and improve cardiac function, and the chylothorax was subsequently cured by complete removal of the cardiac myxoma without recurrence during a 6-month follow-up period, which further demonstrated that the left atrium myxomas caused the chylothorax.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[11][12][13][14] Larger cardiac myxomas may cause similar hemodynamic abnormalities resulting in chylothorax. 15 In our case, the left atrial myxoma can float through the mitral valve into the left ventricle during diastole, causing mitral orifice obstruction like rheumatic mitral stenosis, which can gradually or suddenly result in congestion of systemic circulation and obstruction of lymphatic return, and eventually cause chylothorax. Furthermore, the chylothorax improved after oral diuretics were used to reduce pulmonary congestion and improve cardiac function, and the chylothorax was subsequently cured by complete removal of the cardiac myxoma without recurrence during a 6-month follow-up period, which further demonstrated that the left atrium myxomas caused the chylothorax.…”
Section: Discussionmentioning
confidence: 74%
“…The increased pressure of the superior vena cava can cause lymphatic reflux disorders, leading to the development of chylothorax, which is the main mechanism of the heart disease‐related chylothorax mentioned above 11–14 . Larger cardiac myxomas may cause similar hemodynamic abnormalities resulting in chylothorax 15 . In our case, the left atrial myxoma can float through the mitral valve into the left ventricle during diastole, causing mitral orifice obstruction like rheumatic mitral stenosis, which can gradually or suddenly result in congestion of systemic circulation and obstruction of lymphatic return, and eventually cause chylothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Right-sided myxomas are uncommon (15%–20%), and RV (3%–4%) or pulmonary artery myxomas are exceedingly uncommon ( 6 ). Syncope, pulmonary embolism, chest congestion, and sudden death are complications that can result from obstruction of the outflow of blood from the RV ( 2 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another case study reported resection of a right ventricular myxoma of 9.5 × 5.0 cm. However, resection of a ventricular tumor combined with clearance of a pulmonary embolism has not often been reported [ 6 ].…”
Section: Discussionmentioning
confidence: 99%